2021
DOI: 10.20473/jmcs.v10i1.25603
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of SSOP (Standard Sanitation Operating Procedure) in Freezing Process Cuttlefish (Sepia officinalis) in PT. Karya Mina Putra, Rembang, Central Java

Abstract: Quality deterioration is susceptible by marine products, so that proper handling and processing is needed to delay the  activity of pathogenic bacteria. The procedure of handling marine products must be done carefully and fulfill the SSOP requirements to minimize contamination products by eliminating or controling the factors that cause contamination from raw material until the products ready for distribution. Praktek Kerja Lapang was held in PT. Karya Mina Putra, Rembang, Central Java on December 23, 2019 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…However, neither of these is ideal for the large-scale adoption of eumelanin envisioned by the above applications. The dominant animal source of eumelanin is ink from the typically wild-caught cuttlefish Sepia officinalis , but along with rising ethical concerns, this ties the availability of eumelanin to the harvest of cuttlefish, which varies seasonally and whose processing requires adherence to strict sanitation protocols to avoid contamination with pathogens (d'Ischia, 2018 ; Ristyanti & Masithah, 2021 ). Chemical synthesis methods to produce eumelanin exist, but previous research has demonstrated that their chemical structures differ from those of naturally derived eumelanin (Ito, 1986 ; Pezzella et al., 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, neither of these is ideal for the large-scale adoption of eumelanin envisioned by the above applications. The dominant animal source of eumelanin is ink from the typically wild-caught cuttlefish Sepia officinalis , but along with rising ethical concerns, this ties the availability of eumelanin to the harvest of cuttlefish, which varies seasonally and whose processing requires adherence to strict sanitation protocols to avoid contamination with pathogens (d'Ischia, 2018 ; Ristyanti & Masithah, 2021 ). Chemical synthesis methods to produce eumelanin exist, but previous research has demonstrated that their chemical structures differ from those of naturally derived eumelanin (Ito, 1986 ; Pezzella et al., 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the observation results, it was found that the construction in the form of a floor did not have a good slope, so there was a pool of water when the fish was watered, and the walls formed an angle so that the remaining dirt was not easy to clean. According to Ristyanti and Masithah [6], the floor in the process room needs to have a slope towards the drain to prevent stagnant water, and between the floor and the wall does not form a dead angle.…”
Section: Fig 3 Results Estimation Test Of Ecolimentioning
confidence: 99%
“…Sistem pengendalaian mutu diterapkan melalui SSOP atau Standard Sanitation Operating Procedure yang merupakan suatu proses aplikasi standar prinsipprinsip manajemen yang diterapkan melalui tindakan sanitasi dan higienis. Sistem pengendalian mutu melalui SSOP wajib diterapkan oleh industri dalam menjaga dan meningkatkan kualitas atau mutu produk (Ristyanti & Masithah, 2021). Perusahaan makanan dan minuman dituntut untuk mampu memberikan ketertelusuran terhadap produk yang diolahnya mulai dari petani hingga menjadi produk yang siap konsumsi (Liu et al, 2020).…”
Section: Pendahuluanunclassified
“…Dalam penelitian disebutkan bahwa penyimpanan bahan toksin dan kimia harus tempatkan pada ruang terpisah dengan area proses. Kemasan yang digunakan pun harus aman dari segala cemaran, bersih, dan bermutu baik (Ristyanti & Masithah, 2021). Penyimapan bahan kemasan dan bahan kimia harsu terpisah agar tidak terjadi migrasi senyawa volatil pada bahan kimia ke dalam bahan pengemas.…”
Section: E) Proteksi Dari Bahan Kontaminanunclassified